Analisis Kebijakan Dana Desa dengan Sumber-Sumber Lain Pendapatan Desa dan Ketersedian Fasilitas Pendidikan Terhadap Tingkat Kemiskinan Desa Kabupaten Bogor - Cupian Cupian; Moch. Ihsan Maulana Sa'ban; Ahmad Luqman Hakim (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Structural poverty is rural poverty that has a longterm effect on poverty. This poverty occurs due to changes in the economic structure. The failure of the industrial sector to absorb labor from the agricultural sector raises the problem of unemployment and a decrease in wages for agricultural sector workers. Economists’ opinion that poverty will move from rural to urban areas, then when rural poverty decreases, it has an impact decreasing urban poverty. This study focuses on the factors affecting rural poverty, while the purpose of this study is to see the impact of the village fund program on rural poverty using the difference in difference method and to see how village funds program, allocation of village funds, local tax for village, local retribution for village and the numbers of educational facilities in villages are affecting rural poverty. The research data is in the form of a panel consisting of 416 villages in Bogor Regency with a time series of two years. Furthermore, the data is processed using the ordinary least square approach. The results of the analysis show that the village funds program has an ineffective impact in reducing rural poverty, while the allocation of village funds, local taxes for villages, and local fees for villages have a significant effect with a negative relationship.